Vision-based 3D part recognition system for flexible manufacturing cell - Ismail, Napsiah; Abdul Rahman, Khairuddin; Md Yusof, Juraina; Mohd Kassim, Muhammad Saufi; Tang, Sai Hong; Samin, Razali (2005)
Over the past decade, manufacturing has seen the gradual rise in the used of robots with vision in Flexible Manufacturing Cell (FMC). However, with escalating pressure being placed on industry to increase efficiency, to continually improve and maintain the level of quality, and to reduce cost, a few issues on the FMC such as its flexibility and intelligence has arisen. Nowadays, most of the computer vision in manufacturing is based on the recognition of 2D images that require parts or objects presented in a fixed position or orientation, in which has limited the flexibility of the vision system. Hence, the need to improve the computer vision of the FMC from the acquired multiple 2D images is discussed in this paper. The automatic generation of the 3D objects/parts recognition algorithm and the intelligent based part recognition for FMC will be developed from the multiple 2D images.